IMPLEMENTASI PENGEMBANGAN EKOWISATA DI KABUPATEN BANYUWANGI (STUDI KASUS OBYEK WISATA KAWAH IJEN) - , I Putu Dharmanu Yudartha ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Development in the area should be able to explore the potential of winning. Development of the tourism sector into discourse appeals to the area, especially for areas that have the potential of nature. But tourism development occurs in natural damage prone it is necessary the development of tourism towards ecotourism. Ecotourism, better known as the concept of sustainable tourism with the tourism development also involves with the community around tourist attractions. The concept of ecotourism is expected to have a significant impact to the community because it not only offers natural beauty also performed with fusion of cultural tourism. So this becomes interesting for tourists, and later also had a significant impact on the economy of the area with increasing tourist visits. Ijen has a rich natural and cultural potential around the region, this is offered in the form of ecotourism. The research method used is the descriptive, where the author of the research study with the positivistic approach. The Data used in this research is the primary data and secondary data. Primary Data is processed from the results of interviews and observations in the field. While the secondary data is processed according to existing documentation of IE, RPJMD as well as document RIPD other related to this research.Â Based on the results of the analysis, the results obtained in the process of implementation of ecotourism in the region, has not been running Ijen optimal only focusing on the improvement of the road while the sector of conservation, education, and tourism. For sectors of the economy and society in the development of ecotourism pastisipasi, needs improvement of focus financial resources by giving more space for the community so that more in the future, capable of inflicting multifier effect.Further development of ecotourism less effective because of the related communication socialization has not been going well, then more financial resources are focused on promotion and improvement of roads, and attitudes and behaviors tend to vary no synergy. That means more running ecoutourism development on their own from the parties involved because again the difference of views between the government and management that have not been effective implementation of ecoutourism. As input for improvements in the future, then the recommended implementation ecotourism some things were as follows: 1) More emphasis on public participation around